ASUHAN KEBIDANAN PADA INPARTU KALA I FASE AKTIF DENGAN PENERAPAN BIRTH BALL UNTUK MENPERCEPAT PERSALINAN - hayati, Cut diva kemala; Julianti, Rina; Zahara, Evi; Yushida, Yushida (SINERGI : Jurnal Riset Ilmiah, 2025)
Introduction: Prolongation of the first stage is one of the problems that often occurs in the labor process. The active phase of the first stage is one of the most important phases of labor progress, therefore every birth attendant must be able to control and supervise the labor process so as not to enter a pathological situation. Birthing ball is one of the active birth methods using a pilates ball that helps mothers in the first stage of labor. The use of a pilates ball with various positions can help speed up the duration of the first stage of labor. According to Ramadhani's research (2022), the use of the birthing ball method can provide progress in the first stage of labor in mothers in labor, where the estimated birth of the first child is above 12 hours, but using the birthing ball method the estimated birth is between 8-10 hours. Objective: to speed up labor with the Birth Ball in Mother M G1P0A0. Research method: descriptive with a case study approach. The subject of the study was a 23-year-old mother M G1P0A0, at 40 weeks 1 day of pregnancy with a dilation of 6. This study was conducted on March 2, 2025. Results: The results of the study showed that there was a significant difference in the method carried out by Mother M G1P0A0 with the birthing ball method faster than the method estimated by physiology in the first child, which is between 10-12 hours, while the study was only at 5-10 hours. Conclusion: It is hoped that the Birth ball application care can be proven to accelerate labor and can be applied periodically at PMB Dewi Sandra Lubis